Keutel Syndrome, a Review of 50 Years of Literature - Cancela, M. Leonor; Laizé, Vincent; Conceição, Natércia; Kempf, Hervé; Murshed, Monzur (Frontiers in Cell and Developmental Biology, 2021)
Keutel syndrome (KS) is a rare autosomal recessive genetic disorder that was first identified in the beginning of the 1970s and only nearly 30 years later attributed to loss-of-function mutations in the gene coding for the matrix Gla protein (MGP). Patients with KS are usually diagnosed during childhood (early onset of the disease) and the major traits include abnormal calcification of cartilaginous tissues resulting in or associated with malformations of skeletal tissues (e.g. midface hypoplasia and brachytelephalangism) and cardiovascular defects (e.g. congenital heart defect, peripheral pulmonary artery stenosis and in some cases arterial calcification), but also hearing loss and mild mental retardation. While studies on Mgp-/- mouse, a faithful model of KS, show that pathologic mineral deposition (ectopic calcification) in cartilaginous and vascular tissues is the primary cause underlying many of these abnormalities, the mechanisms explaining how MGP prevents abnormal calcification remain poorly understood. This has negative implication for the development of a cure for KS. Indeed, at present, only symptomatic treatments are available to treat hypertension and respiratory complications occurring in the KS patients. In this review, we summarize the results published in the last 50 years on Keutel syndrome and present the current status of the knowledge on this rare pathology.